Interleaving Carbon-Glass veil in glass epoxy composite for improved mode-I fracture toughness A hybrid approach - Vinayak S. Uppin; P. S. Shivakumar Gouda; I. Sridhar; Aravind Muddebihal (Fracture and Structural Integrity)
The present study investigates the influence of hybrid interleaving technique using Glass and Carbon veils to improve the mode-I fracture toughness in Glass epoxy laminates. Commercially available non-woven Carbon and Glass veils with different areal densities were used to develop hybrid interleaved composites. Two approaches of interleaving, namely inter-ply and inter-weaved veils, were followed to manufacture the interleaved composite laminates using the hand layup technique. Double Cantilever Beam (DCB) samples were tested to estimate the interlaminar fracture toughness (IFT). Test results indicate that the inter-ply interleaved composite (I-C30G30) exhibited an improved initial and propagation fracture toughness of about 16.98% and 3.08%, respectively. A decreased IFT during initiation and propagation was observed for I-C15G30 and I-C20G30 when compared to plain samples. In case of inter-weaved veil interleaving approach, an improved fracture toughness (GIC and GIP) of about 7.96% and 12.94%, respectively, was observed for W-C15G30 sample, nevertheless W-C20G30 and W-C30G30 showed a drop in fracture toughness (GIC) of an about 12.15% and 9.22%, respectively, and an improvement in fracture toughness (GIP) of about 12.37% and 13.82%, respectively, when compared to plain sample. Scanning electron photo images (SEPI) of cracked laminates witnessed the fracture mechanisms involved in hybrid ply interleaved and non-interleaved composite laminates